2018
DOI: 10.3390/met8110930
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Creep in Alloys Strengthened by Rod-Shaped Particles: Al-Cu-Mg Age-Hardenable Alloys

Abstract: In recent years, a creep model that does not involve adjustable parameters has been successfully applied to coarse-grained aluminum. The main feature of this model is that it is fully predictable. On the other hand, in the case of age-hardenable alloys, any physically-based creep model should take into account the changes in the volume fraction, size and distribution of strengthening precipitates, and the effect of grain size. With this aim in view, in this paper, the original model previously applied to singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As reported in Ref. 27) that the spherical particles can lower the minimum creep rate than the rod-like ones. As shown in Fig.…”
Section: Discussionmentioning
confidence: 53%
“…As reported in Ref. 27) that the spherical particles can lower the minimum creep rate than the rod-like ones. As shown in Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Al-Cu and Al-Cu-Mg alloys are widely used in the aircraft industry due to their excellent mechanical properties, which depend on the fine dispersion of secondary phase strengthening precipitates [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [21] found that the dimensional stability of an Al-Cu-Mg alloy can be improved by stress-aging. Paoletti et al [22] and Li et al [23] modeled the creep behavior of an aged Al-Cu-Mg alloy. Li et al [24] discussed the synergy influence of pre-straining and Si addition on microstructures of Al-Cu-Mg alloys.…”
Section: Introductionmentioning
confidence: 99%